(untitled) (Balthazar, 2022)
Is there a morally relevant distinction between cases in which the agent harms someone and cases in which she merely allows someone to be harmed? Holding that such distinction exists and is morally relevant has implications on both theoretical and practical grounds. In my paper, I discuss one of the most conspicuous defences of the existence of the distinction between doing and allowing harm (from now on, DAH). I argue that – provided that it be possible to establish such a distinction – what really matters is whether and how this distinction would be morally relevant. The moral relevance of such distinction is, in fact, much controversial. The main reason why the DAH should be morally relevant is that it legitimizes the agents’ authority over their own resources. I address two main issues: the problem of injustice within the DAH and the conservative account of personal identity held by the advocates of DAH. Regarding the problem of injustice, I argue that when confronted with a practical problem such as the obligation to give money to charity, the DAH seems to imply that those in miserable conditions deserve it. Such a position seems to be untenable from both an ethical and a metaphysical point of view. I then discuss the notion of personal identity that would benefit from the DAH in the light of some psychoanalytic concepts. The fact of legitimizing the agents’ ownership of their own resources does matters because it allows them to fulfil those projects that constitute their Ego-Ideal. In other words, the DAH encourages the agents to become the person they already aspire to be. Such perspective delineates a particularly conservatory way of thinking about ethics which may be rejected for several reasons. One could, for instance, argue that ethics should encourage agents not to stick to their old identity but rather to question it and adapt it when new problems arise.